Artificial Intelligence: Socio-Political Challenges of Delegating Human Decision-Making to Machines - Robert Braun (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2019)
Artificial intelligence is at the heart of current debates related to ethical, social and political issues of technological innovation. This briefing refocuses attention from the techno-ethical challenges of AI to artificial decision-making (ADM) and the questions related to delegating human decisions to ADM. It is argued that (a) from a socio-ethical point of view the delegation is more relevant than the actual ethical problems of AI systems; (b) instead of traditional responsible AI approaches focusing on accountability, responsibility and transparency (ART) we should direct our attention to trustworthiness in the delegation process; and (c) trustworthiness as a socio-communicational challenge leads to questions that may be guided by a responsible research and innovation framework of anticipation, reflexivity, inclusion, and responsiveness. This may lead to different questions policymakers and other interested publics may ask as well as novel approaches, including regulatory sandboxes and other measures to foster a more inclusive, open and democratic culture of human-ADM relations.
Keywords: M14; M31; O31; O32; O33; 330; AI; arithmetic decision-making; delegation; Arendt; RRI